2019
DOI: 10.1002/gps.5131
|View full text |Cite
|
Sign up to set email alerts
|

The impact of military service on the mental health of older UK veterans: A qualitative study

Abstract: Background There may be ongoing psychological problems associated with military service later in life; yet as the elderly in the general population also suffer from mental health problems, whether such issues can be attributed to military service or are a feature of ageing remains unclear. This study aimed to explore veteran and nonveteran perceptions of the impact of their occupation on their psychological well‐being later in life. Methods Twenty‐five veterans (≥65 y); 25 nonveterans (≥65 y); 10 veterans with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In addition, the wealth of information in the CHARLS data facilitates us to elucidate possible mechanisms of the positive health effect of military service in the elderly. The mechanism analysis enriched previous related studies (e.g., Landes et al, 2017;McKinney et al, 1997;Williamson et al, 2019). Moreover, the results support the finding that military service promoted human capital (e.g., Eynde, 2015;Hou et al, 2020;Lindqvist & Vestman, 2011;MacLean, 2017), while we found that some social security measures were ineffective in improving the health status of older veterans.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, the wealth of information in the CHARLS data facilitates us to elucidate possible mechanisms of the positive health effect of military service in the elderly. The mechanism analysis enriched previous related studies (e.g., Landes et al, 2017;McKinney et al, 1997;Williamson et al, 2019). Moreover, the results support the finding that military service promoted human capital (e.g., Eynde, 2015;Hou et al, 2020;Lindqvist & Vestman, 2011;MacLean, 2017), while we found that some social security measures were ineffective in improving the health status of older veterans.…”
Section: Introductionsupporting
confidence: 87%
“…Risk events directly related to soldiers’ health include training accidents, overtraining injuries, public security maintenance, and major emergency events such as infectious diseases and natural disasters (Chase et al, 2015; Elder et al, 2009; McKinney et al, 1997; Wilmoth et al, 2010; Zhao & Guo, 2022). Especially in nonpeaceful times, soldiers would face significant risks disability, chronic illness, and mental illness (Bedard & Deschênes, 2006; Chase et al, 2015; Davies et al, 2015; Dobkin & Shabani, 2009; Williamson et al, 2019), and may even give their lives. Also, some studies provided evidence of higher mortality rates among veterans who have served in combat (Johnston et al, 2016; Landes et al, 2017; Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%